A SIMPLIFIED METHOD FOR THE EXTRACTION OF RECOMBINANT TAQ DNA POLYMERASE FROM ESCHERICHIA COLI - TURAN, KADİR (SLOVAK UNIV AGRICULTURE NITRA, 2018)
DNA polymerase (Taq) enzyme isolated from Thermus aquaticus, a thermostable gram-negative bacterium, is a basic component of PCR, widely used in life sciences. The extraction and purification of this enzyme involves time-consuming and expensive steps such as precipitation of proteins with PEI and/or ammonium sulfate, column chromatography techniques, and removal of salts or other small molecular weight contaminants by dialysis. In this work, a novel and simplified method for extraction and purification of the recombinant Taq polymerase from Escherichia coli was employed, which used cold acetone instead of PEI or ammonium sulfate to precipitate the enzyme. The enzyme was efficiently recovered as active form from both the crude cell lysate and column fractions with cold acetone precipitation. This simplified method enabled us to obtain high quality Taq DNA polymerase in a much shorter time and at a lower cost.
Keywords: Taq DNA polymerase; Acetone precipitation; PCR; Thermus aquaticus; ENZYMATIC AMPLIFICATION; RAPID PURIFICATION; EXPRESSION; BINDING; GENE; TEMPERATURE